Autonomous demand and the investment share - Daniele Girardi; Riccardo Pariboni (University of Massachusetts, Department of Economics, 2018)
This paper looks at the effect of demand shocks on the investment share of the economy. Using panel data on 20 OECD countries, we show that the rate of growth of autonomous demand (exports, public spending and housing investment) is positively correlated with subsequent values of the share of business investment in GDP. By means of an instrumental-variables strategy, we confirm a positive effect of demand dynamics on the business investment share. We instrument autonomous demand with US demand for imports interacted with exposure to trade with the US, openness to trade of a country's main export destinations, and military spending. A permanent 1% increase in autonomous demand growth raises the investment share by 1.5 to 1.9 percentage points of GDP in our preferred panel IV specification. Our results provide empirical support for the view that the influence of aggregate demand on capital accumulation can be a major source of hysteresis. Our results are inconsistent with the canonical New Keynesian 3-equations model, the Neo-Kaleckian model with flexible equilibrium utilization and Classical-Marxian growth models. A positive influence of autonomous demand on the investment share is instead compatible with demand-led models in which capacity adjusts to demand in the long-run.
Keywords: C26; E11; E12; E22; O41; 330; Hysteresis; Investment; Demand-led Growth; Capacity Adjustment; Supermultiplier